Analisis Dan Perancangan Antarmuka Situs Portal Belajar Bagi Penyandang Dyschromatopsia - Sumolang, Philip Andrew; Delima, Rosa; Suwarno, Sri (Jurnal Ilmiah FIFO, 2023)
Currently, many learning websites have been developed to assist people in self-learning from home. However, the developed learning websites are not yet user-friendly for individuals with dyschromatopsia. This is due to the design process not considering using colors that are easily distinguishable for users with dyschromatopsia. Based on the issues, a learning portal website interface that is friendly to individuals with dyschromatopsia is needed. In the design of this application, the method used is User-Centered Design (UCD). Through the UCD method, the needs of users with dyschromatopsia become the main focus of the research. Testing is conducted through usability testing using the Overall Relative Efficiency, Completion Rate, and the System Usability Scale (SUS) questionnaire to measure user satisfaction. The test results show an Overall Relative Efficiency value ranging from 72.675% to 92.130%, Completion Rate testing yields an effectiveness value range of 82% to 96%, and SUS testing yields a score of 81.25. In addition, the author also conducted testing for color-blind accessibility, which resulted in the finding that the contrast ratio of all the pages on the CourseHack website meets the minimum contrast ratio standards.